2021
DOI: 10.3390/ijms22073662
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Independent Initiation during Cap-Independent Translation of m6A-Modified mRNA

Abstract: The methylation of adenosine in the N6 position (m6A) is a widely used modification of eukaryotic mRNAs. Its importance for the regulation of mRNA translation was put forward recently, essentially due to the ability of methylated mRNA to be translated in conditions of inhibited cap-dependent translation initiation, e.g., under stress. However, the peculiarities of translation initiation on m6A-modified mRNAs are not fully known. In this study, we used toeprinting and translation in a cell-free system to confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, it was shown that the wide-spread m 6 A modification in the 5 -UTRs of many messengers enables cap-independent translation under stress conditions [16]. In this Special Issue, Sakharov et al confirm this earlier observation using in vitro translation and toeprinting assays [3]. Furthermore, they find that, while under normal conditions, the initiation and elongation on a methylated mRNA are less efficient, the presence of m 6 A in the 5 -UTR makes the initiation more resistant to the inhibition of the canonical cap-dependent scanning.…”
mentioning
confidence: 65%
“…For example, it was shown that the wide-spread m 6 A modification in the 5 -UTRs of many messengers enables cap-independent translation under stress conditions [16]. In this Special Issue, Sakharov et al confirm this earlier observation using in vitro translation and toeprinting assays [3]. Furthermore, they find that, while under normal conditions, the initiation and elongation on a methylated mRNA are less efficient, the presence of m 6 A in the 5 -UTR makes the initiation more resistant to the inhibition of the canonical cap-dependent scanning.…”
mentioning
confidence: 65%
“…Modifications in 5' and 3' UTRs as well as deregulation of enzymes involved in cap formation or cap-binding proteins can affect the integrity or availability of the 5' cap. [65][66][67] This disruption can interfere with the recruitment of translation initiation factors like eIF4E and impair the assembly of the translation initiation complex. Besides, dysregulated miRNA expression, modification or aberrant alternative splicing of mRNA, can lead to abnormal translation inhibition or activation of specific genes.…”
Section: Regulation Of Translation Initiationmentioning
confidence: 99%
“…Recently, a firefly luciferase assay was used to demonstrate that m6A-mediated translation initiation is less efficient compared to cap-dependent initiation [ 31 ]. On the other hand, this approach demonstrated comparable results in comparison to IRES-mediated translation initiation [ 32 ].…”
Section: Translation Initiation Mechanismsmentioning
confidence: 99%